A resistance change effect in perovskite CH3NH3PbI3 films induced by ammonia. Issue 84 (7th September 2015) - Bao, Chunxiong; Yang, Jie; Zhu, Weidong; Zhou, Xiaoxin; Gao, Hao; Li, Faming; Fu, Gao; Yu, Tao; Zou, Zhigang
Abstract : The resistance of the perovskite CH3 NH3 PbI3 film can change significantly in seconds induced by NH3 at room temperature. Abstract : The resistance of the perovskite CH3 NH3 PbI3 film was found to decrease significantly in seconds when the film was exposed to an NH3 atmosphere at room-temperature, and recover to its original value in seconds when out of the NH3 environment.